PERBANDINGAN JUMLAH TROMBOSIT PADA DIABETES MELITUS TIPE 2 DENGAN KOMPLIKASI VASKULAR DAN TANPA KOMPLIKASI VASKULAR DI RSUP PROF. DR. R. D. KANDOU - Widiarto, Nina S; Posangi, Jimmy; Mongan, Arthur; Memah, Maya (e-Biomedik, 2013)
Abstract: Diabetes mellitus (DM) is a degenerative disease which has increased from year to year. Type 2 diabetes has the highest number of cases. There is a change in platelet count in type 2 diabetes. The change in platelet count can lead to vascular complications in DM. This was a descriptive analytic study with a cross sectional design by using the medical record data of type 2 diabetic patients in the outpatient department of Prof. DR. R. D. Kandou Hospital, Manado. Subjects who met the inclusion criteria were 72 patients; 36 patients with vascular complications and 36 patients without vascular complications. Data were analyzed by using the Mann-Whitney test to determine the ratio of the platelet count in patient with type 2 diabetes patient with and without vascular complication, with Î± = 0.05. The Mann-Whitney test showed that there was no significant difference in platelet count among patients with type 2 diabetes, with and without vascular complication (P = 0.051). Conclusion: There was no significant difference in the platelet count of type 2 diabetes patients with and without vascular complication.Keywords: type 2 diabetes mellitus, vascular complication, platelet countAbstrak: Diabetes Melitus (DM) merupakan salah satu penyakit degeneratif yang semakin meningkat jumlahnya dari tahun ke tahun. Jenis DM yang paling banyak kasusnya ialah DM tipe 2. Pada DM tipe 2 terjadi perubahan jumlah trombosit, yang dapat menyebabkan terjadinya komplikasi vaskular pada DM. Penelitian ini bersifat deskriptif analitik dengan rancang penelitian cross sectional dengan menggunakan data rekam medik pasien DM tipe 2 yang rawat jalan di RSUP Prof. DR. R. D. Kandou Manado. Subjek penelitian yang memenuhi kriteria inklusi berjumlah 72 pasien; 36 pasien dengan komplikasi vaskular dan 36 pasien tanpa komplikasi vaskular. Hasil penelitian diuji menggunakan uji Mann-Whitney untuk mengetahui perbandingan jumlah trombosit pada pasien DM tipe 2 dengan komplikasi vaskular dan tanpa komplikasi vascular, Î± = 0,05. Uji Mann-Whitney menunjukkan bahwa perbedaan jumlah trombosit tidak bermakna antara pasien DM tipe 2 dengan komplikasi vaskular dan tanpa komplikasi vaskular (p=0,051). Simpulan: Tidak terdapat perbedaan bermakna antara jumlah trombosit pada pada DM tipe 2 dengan komplikasi vaskular dan tanpa komplikasi vaskular.Kata kunci: DM tipe 2, komplikasi vaskular, jumlah trombosit